14+3n=-3(n-4)

Simple and best practice solution for 14+3n=-3(n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+3n=-3(n-4) equation:


Simplifying
14 + 3n = -3(n + -4)

Reorder the terms:
14 + 3n = -3(-4 + n)
14 + 3n = (-4 * -3 + n * -3)
14 + 3n = (12 + -3n)

Solving
14 + 3n = 12 + -3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '3n' to each side of the equation.
14 + 3n + 3n = 12 + -3n + 3n

Combine like terms: 3n + 3n = 6n
14 + 6n = 12 + -3n + 3n

Combine like terms: -3n + 3n = 0
14 + 6n = 12 + 0
14 + 6n = 12

Add '-14' to each side of the equation.
14 + -14 + 6n = 12 + -14

Combine like terms: 14 + -14 = 0
0 + 6n = 12 + -14
6n = 12 + -14

Combine like terms: 12 + -14 = -2
6n = -2

Divide each side by '6'.
n = -0.3333333333

Simplifying
n = -0.3333333333

See similar equations:

| 16+.20x=30 | | -3y+28=ysq | | -2(w-7)+12w=34 | | 23c+20=29c+74 | | 8=17.666c | | 16+.20x=306 | | 6(x+3)=-5 | | 11.1x-3.3=-8.3x+6.4 | | A+2b=20+c | | 5y-2=-(y+5) | | 15-5w=75-10w | | (3x+7)(x+6)=0 | | 325x+6=421 | | (cos^2)(x)-(4)(cosx)-5=0 | | 3(4x+6)-5=12x+13 | | x^2+y^2+10x+2y+13=0 | | 2(2x)+2(x)=210 | | X+20=9x-4 | | 45.75x+3.50=35.95x+4.75 | | 2(a-6)+11=25 | | A+2b=20c | | y^2P^2+xP+y=0 | | factorisex^2+y^2+10x+2y+13=0 | | 3(2x-3)=5x-5 | | x^2+181=0 | | y^2P^2-xP-y=0 | | 25+3x=18 | | X-38=106 | | X+12=-12+X | | y-40=73 | | d=3.5(s-5) | | P^2-xP-y=0 |

Equations solver categories